Metropolitan governance in the context of dynamic urbanization: the case of Brazil - Zimmermann, Karsten; Leonel, Ana Lia; Kontopp, Marcio A. (Frontiers in Political Science, 2023)
This study discusses the evolvement of metropolitan governance in Brazil and uses greater São Paulo as an in-depth case study to demonstrate how metropolitan governance is organized in a megacity region in the Global South. This is of interest as many publications in this specific academic field focus on European or North American city regions that are, on average, smaller in size and part of multi-level governance systems. Hence, many theoretical positions that are established in the scholarly debate do not work well in the context of megacities. The study will describe how the metropolitan governance arrangement in greater São Paulo evolved and reflected on the setbacks and success of metropolitan planning and policies in the context of uncertain state support. Metropolitan regions have been established in Brazil by the military regime in the mid-1970s for industrialization and comprehensive top-down planning. After the fall of the regime in the 1980s, the question of metropolitan regions was delegated to the states which created a sort of institutional vacuum and a lack of dedicated policies. In 2018, however, Brazil had 76 institutionalized metropolitan regions but these differ in size and institutional strength. The metropolitan region of São Paulo is the biggest as it comprises 39 municipalities with approximately 20 million inhabitants. However, given the dynamic of expansion, the question of establishing an appropriate scale emerged. Attempts to create a governance arrangement for regional development and strategic planning for the so-called São Paulo Macrometropolis with 172 municipalities and roughly 32 million inhabitants failed. However, in a separate process, over decades, seven metropolitan regions emerged on a smaller scale (the São Paulo Metropolitan Region being one of them). The study is based on a literature review, document analysis (laws in particular), and workshops with Brazilian colleagues that happened within the context of a research project on environmental planning and water governance in the greater São Paulo Metropolitan Region.